The effect of organizational culture and work motivation on performance of office offices, Cilamaya Wetan, Karawang Regency - Maryam Saniah; Budi Rismayadi; Neni Sumarni (Trigin Publisher, 2022)
This study aims to determine and analyze (1) whether organizational culture and work motivation have a partial effect on the performance of employees at the Cilamaya Wetan sub-district office in Karawang regency (2) whether organizational culture and work motivation have a simultaneous effect on the performance of employees at the Cilamaya wetan sub-district office in Karawang regency. (3) Which variable has the most influence on the performance of the Cilamaya Wetan District Office Employees, Karawang Regency. The research was conducted at the Cilamaya Wetan District Office, Karawang Regency. This research is quantitative. Determination of the sample is done by using a saturated sampling technique (census), which is as many as 45 employees. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results of the study concluded that (1) Organizational Culture and Work Motivation, influenced the performance of the Cilamaya Wetan Office Employees, Karawang Regency. This means that high organizational culture, work motivation and discipline can improve the performance of Cilamaya Wetan District Office Employees, Karawang Regency (2) Organizational Culture and Work Motivation simultaneously have a positive and significant effect on the performance of Cilamaya Wetan District Office Employees, Karawang Regency (3) Work motivation is a variable the most dominant influence on employee performance